Aggregate Attribute-Based Signature Scheme for Scalable and Efficient Cryptographic Systems (International Journal of Scientific Research in Science and Technology, 2025)
Attribute-Based Signatures (ABS) provide a cryptographic mechanism enabling signers to authenticate messages while preserving their privacy, based on a set of attributes. This paper introduces an Aggregate Attribute-Based Signature (AABS) scheme that leverages bilinear pairings to support efficient aggregation of multiple signatures into a compact form. The proposed scheme is designed to address scalability challenges in systems requiring numerous signatures, such as healthcare data sharing, vehicular networks, and blockchain-based applications. The scheme ensures essential security properties, including unforgeability, anonymity, and collusion resistance, under the Bilinear Diffie-Hellman (BDH) assumption. Each signer generates a signature based on their attributes, which can then be aggregated into a single signature for a given message by an authorized entity. Verification is efficient, requiring only a constant number of pairing operations, regardless of the number of signers or attributes involved. A rigorous security analysis demonstrates that the scheme resists forgery attempts and unauthorized collusion, ensuring reliable message authentication even in adversarial settings. Furthermore, the compactness of the aggregated signatures reduces storage and computational overhead, making it ideal for resource-constrained environments. This work paves the way for more scalable, privacy-preserving, and efficient attribute-based cryptographic solutions.